POSSIBILITY OF HYDROGEN SEPARATION FROM SYNTHESIS GAS BY USING THE ABSORPTION PROCESS (Global Journal of Advanced Engineering Technologies and Sciences, 2019)
The present paper deals with a possibility of hydrogen separation from synthesis gas by using the absorption process. The composition of the synthesis gas mixture generated in the process of high-temperature gasification and the possibility of its recovery are analyzed. The risks affecting the life of the metal hydride alloy is also taking into account. The possibility of increasing the hydrogen concentration in the gaseous mixture is exploited by using series-connected pressure vessels and by the gravitational effect. In the conclusion, there is a proposal of connection of separation column applying the principle of hydrogen absorption using MH alloys.